Consenso em reumatologia pediátrica: Parte I - Definiçã o dos critérios de doença inativa e remissão em artrite idiopática juvenil/artrite reumatóide juvenil - Machado, Claudia [UNESP] (2005)
Validated and widely accepted criteria for clinical remission in JIA/JRA do not currently exist. Objective: To achieve consensus in this matter. Methods: The Delphi consensus-formation approach was used to gather the criteria in use by pediatric rheumatologists (PR) worldwide. Results from the questionnaires provided the basis for the development of a consensus conference using the nominal group technique (NGT) to reach consensus on questions not solvable by the questionnaire format. One hundred and thirty PR from 34 countries responded the Delphi questionnaires and 20 PR from 9 countries attended a 2-day consensus conference. Results: Consensus results were: criteria for inactive disease should include: 1) no active arthritis; 2) no fever, rash, serositis, splenomegaly, or generalised lymphadenopathy attributable to JIA/JRA; 3) no active uveitis; 4) normal ESR or CRP (if both are tested, both must be normal); 5) a physician's global assessment of disease activity rated at the best score possible and indicating no disease activity. Conclusions: According to consensus vote, 6 continuous months of inactive disease are necessary before classifying a patient as in remission on medication; 12 months off medication while maintaining inactive disease are necessary to classify a patient as in remission off medication. The criteria for in remission off medications should predict with 95% accuracy that a patient has a 20% probability of disease relapse within the next 5 years.